Biosynthesis of helvolic acid and identification of an unusual C-4-demethylation process distinct from sterol biosynthesis - Jian-Ming Lv (Nature Portfolio, 2017)
The biosynthetic pathway of fusidane-type antibiotics, such as helvolic acid, is largely undiscovered. Here, the authors investigate the biosynthesis of helvolic acid, thereby determining the sequence of the enzymatic reactions involved in the process and the intermediates formed.